Perceptions of hospital pharmacists regarding roles in preventing and minimizing prescribing cascades: a mixed-method study - Asad, Mahnoor; Ullah, Waseem; Gajdács, Márió; Madléna, Melinda; Shanmugham, Suresh; Veettil, Sajesh K; Jamshed, Shazia Q (The Journal of Infection in Developing Countries, 2025)
Introduction: A prescribing cascade occurs when new medications are prescribed to address an adverse drug reaction (ADR) associated with the preceding use of a medication, which may be mistaken as the onset of a novel disease or condition. The aim of this study was to evaluate the perceptions of hospital pharmacists regarding roles in preventing and minimizing prescribing cascades. Methodology: A qualitative, semi-structured interview, followed by a quantitative, questionnaire-based study, was carried out at the Shifa International Hospital (SIH; Islamabad, Pakistan). Discharge summaries of patients aged ≥ 60 years were collected to assess the prevalence of polypharmacy at SIH. Results: Discharge summaries of n = 350 patients were collected; 60.2% (n = 211) had comorbid conditions, and the co-occurrence of diabetes and hypertension were the most common. 37.8% (n = 132) were taking 8 or more medications. Eight (n = 8) hospital pharmacists participated in the qualitative study, and 4 major themes were identified in their perceptions regarding prescribing cascades. Fifty-two (n = 52) pharmacists were recruited in the quantitative phase. 86.5% (n = 45) of the participants reported long standing illness/chronic conditions; 67.3% (n = 35) noted the presence of comorbidities as a high risk, while 90.3% (n = 47) noted multiple prescribers, and 75.0% (n = 39) identified the ageing population as important risks factors for polypharmacy. Conclusions: The current research may inform the role and responsibilities of hospital pharmacists in outpatient and inpatient departments, and in interprofessional care teams, in preventing and minimizing prescribing cascades.